Free Vibration of Cracked Cantilever Beams: Analytical and Experimental Modelling - Kahya, Volkan; Karaca, Sebahat (Fırat University, 2018)
This study presents free vibration of cantilever beams with multiple cracks. The problem is solved analytically by the transfer matrix method, and is validated experimentally by the operational modal analysis. Six damage scenarios are considered to study crack effect on the natural frequencies and corresponding mode shapes. Graphs and tables for numerical results are given and discussed. Results show that crack occurrence in a beam significantly changes its dynamic behavior.
Keywords: Engineering; Mühendislik